Global Attractors of Reaction-diusion Systems and Their Homogenization (Journal of Partial Differential Equations, 2004)
In this paper, we study the existence of the global attractor A" of reaction-diffusion equation ∂_tu^ε(x, t) = A_εu^ε(x, t) - f(x, ε^{-1}x, u^ε(x, t)), and the homogenized attractor A^0 of the corresponding homogenized equation, then give explicit estimates for the distance between the attractor A^ε and the homogenized attractor A^0 .
Keywords: Homogenization; global attractor; reaction-diffusion systems; almostperiodic function; Diophantine conditions